Study on the Urban Conservation by the Sectors of Houses and Villas in the City of Paris and its Suburban Area - Eguchi, Kumi (International Planning History Society Proceedings, 2022)
The Sectors of Houses and Villas (HV sector) in the City of Paris and Montrouge, the suburban city of Paris, are determined by the Local Plan of Urbanism (PLU) based on the SRU Law of 2000 to maintain a favourable residential environment. The purpose of this study was to provide an overview of the HV sector and examine its effectiveness. In comparison with existing historic environment conservation schemes, in terms of conservation approach, the HV sector takes a sustainable approach to maintaining the form and layout of existing buildings through local provisions, such as maximum building area. In the case of the SL Sector, Villa Daviel in Paris, when development pressure increased in the 1990s in the block where the SL sector was located, building restriction zones and height restrictions were established in the block where residential areas were located, based on consensus with the inhabitants, to conserve the entire block. When the transition from POS to PLU was made, height restrictions were set with a view to sustainable form conservation, and easements were established.